Meaning-making of student experiences during outdoor exploration time. Issue 2 (3rd April 2021) - Berg, Stephen; Bradford, Brent; Barrett, Joe; Robinson, Daniel B.; Camara, Fabiano; Perry, Tess
ABSTRACT: The purpose of this study was to gather the thoughts and opinions of students and their teachers around the benefits of outdoor exploration time. Students within three grade 3 classes in one western Canadian province were afforded opportunities to connect with the outdoor elements and each other in designated forested areas near their school, while also enjoying free outdoor learning time. Semi-structured focus group interviews were conducted for participants to share their experiences. Using a thematic approach, four key findings emerged from these interviews: expanding perspectives, connection to nature, sense of choice, and enjoyment. According to the findings, affording an outdoor space and the opportunity for students to spend time outside on a consistent basis may be an important way to give students the chance to learn in an organic way from nature, form deep connections to nature, develop within themselves a sense of choice, and find enjoyment in the natural environment.